LINGUISTIC FEATURES OF THE ENGLISH USED IN SOUTHEAST ASIAN COUNTRIES / Nguyễn Việt Nga; NHDKH PhD Do Kim Phuong - Nguyễn, Việt Nga
This study is conducted aiming at finding out linguistic features of some major varieties of English in Asia such as Philippines English, Malaysian English and Singaporean English in terms of their vocabularies, thus helping Vietnamese people to improve their English proficiency when working in such Asian countries.In order to achieve the aim of the study, three methods including descriptive, contrastive, quantitative and qualitative methods are used in analyzing lexical features of the English used in Malaysia and Singapore. As a result, three major objectives have been achieved: finding out the features of vocabulary in some varieties of English in Asia; pointing out the differences between the vocabulary in some varieties of English in Asia; and giving some possible implications for export labor workers inusing English in Asian countries.With a view to helping the readers have a better understanding oflinguistic features of some major varieties of English in Asia, three varieties of English in Asia named Malaysian English and Singaporean English have been described and analyzed. Regarding the reason why these features exist, the linguistic features in terms of their vocabulary have been found.